Isolation and study of morphological and cultural properties of cyanobacteral community from hot springs in Almaty region (Eurasian Journal of Ecology, 2023)
The diversity of cyanobacteria from four hot springs in the Chundzha settlement, located in the Almaty region, was studied to determine the species composition and isolate axenic cultures of thermophilic cyanobacteria. The objective was to investigate the diversity, morphological and cultural properties of thermophilic cyanobacteria from the Chundzha hot springs, and to establish axenic cultures for potential utilization in biotechnology, as these organisms are scientifically interesting and valuable as a source of thermostable biomolecules. As a result of the study, eight axenic cyanobacteria cultures were isolated and identified as Oscillatoria subbrevis, Phormidium ambiguum, Nostoc commune, Synechococcus elongatus, Synechocystis sp., Tolypothrix tenuis, Anabaena cylindrica and Spirulina fusiformis. Optimal cultivation conditions were also determined: the isolated cyanobacteria cultures exhibited high growth rates when cultivated in BG-11, Zarruk, and Gromov nutrient media at an optimal temperature of 28-36°C, pH 7, and a light intensity of 50 µmol photons m−2s−1.Key words: hot springs, thermophiles, cyanobacterial diversity, isolated axenic cultures, morphological and cultural properties, selection of cultivation conditions, dynamics of growth.